Analysis of Variance and Correlation Study of Chlorophyll-a in North and South Coast of Lombok Island Using Aqua MODIS Image Data - Hendrata Wibisana; Siti Zainab; Zetta Rasullia Kamandang; Muhammad Rusdi (Graduate Program of Syiah Kuala University, 2020)
Chlorophyll-a mapping is widely used in the coastal environment. The mapping results can be utilized as guidance for fishing activities. The presence of chlorophyll-a in phytoplankton is much investigated concerning the existence of fish as a source of livelihood for fishermen around the globe. One method extensively developed is the use of satellite imagery to map the chlorophyll-content in the coastal region from a small area to a global scale, such as Aqua MODIS image data. This study aims to monitor the distribution of chlorophyll-a on the north coast and south coast of Lombok island. Analysis of variance and parametric statistical tests with t-distribution was utilized to examine the correlation between the two types of chlorophyll-a distribution of the coast area, Lombok Island. The result shows that the distribution of chlorophyll-a concentrations on the north coast and the south of the coast is not the same abundance; the south coast of Lombok island has smaller variances, with the concentration distribution is relatively the same. It differs from the north part; the distribution shows less diversity. This result indicates that a reasonably wide interval wherein some coordinates has a relatively diffuse chlorophyll-a concentration with a sufficiently high distribution level. Analysis of variance result also shows that both the north and south coasts have different fertility levels for their coastal waters, which are characterized by the growth rate of chlorophyll-a on the surface water along the coastal region examined